The influence of self-esteem in the relationship of social media usage and conspicuous consumption - Lee, Kar Wai; Osman, Syuhaily (Human Resource Management Academic Research Society, 2019)
To-date, conspicuous consumptions in both developed and developing countries remain on the rise. As a developing country, there is no exception for Malaysia. The luxury goods sector in Malaysia has been growing along with the rest of the world over the past thirteen years. Current research aimed to investigate conspicuous consumption through examining it from social media usage perspectives and the moderating role of self-esteem of consumers in the relationship between social media usage and conspicuous consumption. The framework of this study suggests that social media platform can cause social comparison among consumers, which the comparison domains are, wealth, status and attractiveness. These comparisons can lead to increasing motivation of acquisition of luxurious products and conspicuous consumption. The study also suggests that difference of high and low self-esteem is moderating the proposed relationship of social media usage and the propensity to consume conspicuously. A survey technique was conducted among 387 consumers using mall-intercept method at selected shopping malls to collect required data for analyses and the sample obtained consisted of Malaysian social media users aged above 18. Multiple regression and PROCESS analyses were conducted to test the correlation between social media usage and conspicuous consumption and moderation of self-esteem as proposed in the research framework. The result obtained indicates that social media usage has significantly influenced conspicuous consumption; and self-esteem was found significantly moderating the relationship between social media usage and conspicuous consumption. Overall, this study provides valuable insights on the understanding of conspicuous consumption and related variables that are influencing it such as social media usage and self-esteem. Consumers and authorities can benefit from these results to create awareness regarding the impact of these variables to ensure better purchase decision to be made by consumers.